Rapid assessment of butterfly diversity of two proposed Community Resource Management Areas (CREMAs) in the Western North Region of Ghana: Implication for conservation - Rosina Kyerematen; CHRISTIANA NAA DEEDEI TETTEY; ROGER SIGISMUND ANDERSON (Society for Indonesian Biodiversity, 2020)
Abstract. Tettey CND, Anderson RS, Kyerematen R. 2020. Rapid assessment of butterfly diversity of two proposed Community Resource Management Areas (CREMAs) in the Western North Region of Ghana: Implication for conservation. Biodiversitas 21: 3699-3706. Community Resource Management Areas (CREMAs) are non-reserved land masses with local communities living in them that contain important components of biodiversity and are open to free access. Biodiversity in these off-reserve areas in Ghana is fast depleting due to unsustainable anthropogenic activities. The Rapid Biodiversity Assessment (RBA) method was conducted in the proposed Manzan and Yawmatwa CREMAs in Sefwi-Debiso; in the Western North Region of Ghana using butterflies as indicator taxa to estimate species richness and diversity in two proposed CREMAs to prioritize these rapidly diminishing forest areas for conservation. A total of 1,352 individual butterflies were recorded at the end of a two-week rapid assessment; with 83 species belonging to five families (Nymphalidae, Papilionidae, Pieridae, Lycaenidae, and Hesperiidae). The findings of the study revealed that 38.5% of the butterfly population belongs to species associated with severe forest disturbance; indicating that these ecosystems are gradually being threatened by ongoing anthropogenic activities. Management efforts aimed at butterfly conservation should be geared towards protecting these proposed CREMAs from excessive human disturbances.